北極理事會形成的研究：加拿大的領導和中國的反應 - 史智文; Smith, Stephen (2015)
碩士 國立政治大學 亞太研究英語碩士學位學程(IMAS) 102926034 三十年前北極是一塊具有爭議的領土，許多國家因此在這塊土地產生許多衝突，鮮少透過國際合作的方式解決爭議，今日許多國際政權採取相互合作來處理爭議，在這些政權中北極理事會是最有影響力的，但是怎麼演變到這樣的呢？ 這篇論文認為原因是中等強國的參與，並藉由加拿大的參與來探討北極理事會的形成，研究結果發現諸多加拿大領導人相互合作並說服反對政權的意見共組北極理事會，此研究也同時發現中等強國對政權的組成有極重要的影響，此論文的第二部份檢視中國對北極理事會的反應，此論文發現中國對北極策略採取國際法，而在此同時他們企圖在北極理事會中增進自身的影響力，總歸上述此研究在分析上有三項主要發現：中國作為外來政權的反應、中國對北極議題採取法律規範、中國對加拿大的北極主權看法。 Thirty years ago the Arctic was a desolate region marked by territorial disputes, mutual suspicion between regional powers, and a complete lack of international cooperation. Today, the Arctic has become a hotbed of cooperation with a mosaic of international regimes governing regional affairs. The Arctic Council has emerged as the most important regime governing Arctic affairs. How did this transformation take place? This thesis argues that middle powers are crucial to regime formation. It examines the role that Canada played in the formation of the Arctic Council. It finds that several Canadian individual leaders acted collectively to bring together the Arctic states and overcome initial resistance in forming the Arctic Council. This study shows that middle powers have the ability to significantly influence regime formation. The second part of this thesis will examine China’s response to the Arctic Council. By surveying the statements of Chinese Arctic officials, it finds that China’s emerging Arctic strategy is to continually stress adherence to international law in Arctic affairs to assuage concerns about China’s Arctic activities while at the same time advocating for a greater decision-making role in Arctic governance for non-Arctic states. An analysis of China’s response to the Arctic Council also reveals three key findings of China’s Arctic cooperation: China’s response in relation to its status as an “outsider” to Arctic affairs, China’s support for the Arctic Council’s transformation from soft law to hard law, and China’s view on Canada’s Arctic sovereignty. 1. Introduction 1\n2. Hypothesis and Methodology 3\n3. Regime Theory: ...